Characteristics and Productivity of Some Pigeon Breeds in Bangladesh (Aves: Columbidae) - Ashraful Kabir (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
This is our hurried responsibility to introduce those pigeon breeds that have economic value. In this case, very common and productive breeds but moderately unknown in history or confusing on their scientific identity need to be focused elaborately. A survey in the country, as well as experiences on these pigeons, inspired to write this valuable fundamental composition. Pet shops, markets, and lofts have sulli (moos-sulli), chuva chandan (chua chandan), bombai (sotobanca/Italian crested mondain), kokah (laugher), and parvin (Australian red) pigeons are carrying a remarkable productivity in the country. Prices of adult and squabs are reasonable to all sorts of people.